GENDER DAN KONFLIK DALAM POLITIK INTERNASIONAL - Bintarsari, Nuriyeni (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2009)
Conflict in international politic is a study’s field related with Peace and Conflict Studies. Conflict Study became critical if we want to analyze many conflicts in many parts of the world nowadays, where million civilian, mainly women and children become victim of conflict violence. Woman Position at political domain, national or international become one study mainstream, but studies in this field (international conflict) still rare. This article want to review studies about conflict and peace, gender position in Politic/International (relation) studies, also offers Israel-Palestine conflict at the end of 2008 and beginning of 2009 as study’s focus example.